psbA-trnH Intergenic Spacer profile of Wax Apple (Syzygium samarangense (Blume) Merr. & L.M. Perry) Cultivars - Tiara Dwi Meilina; Syifara Chika; Muhammad Rifqi Hariri; Asri Febriana; Arnia Sari Mukaromah (Jurnal Ilmu Pertanian Indonesia, 2024)
The fruit known as wax apple, scientifically named Syzygium samarangense (Blume) Merr. & L.M. Perry, is a well-liked agricultural product originating from Demak Regency in the Central Java Province. When it is difficult to distinguish between different forms of an organism, using DNA barcoding to authenticate the identity of species based on their DNA is an important way. The psbA-trnH intergenic spacer is a commonly used molecular approach to analyse the genetic characteristics of plant species. This study investigated the psbA-trnH intergenic spacer profile of wax apple cultivars from Demak regency. The investigation revealed that the psbA-trnH intergenic spacer sequences of the S. samarangense cultivars, namely Madu Thailand and Madu Deli Hijau, had lengths of 535 and 492 base pairs, respectively. Both cultivars demonstrate a greater nucleotide composition of deoxyadenylic acid (A) and deoxythymidylic acid (T) in comparison to deoxycytidilic acid (C) and deoxyguanylic (G). The genetic distance between S. samarangense ‘Madu Thailand’ and ‘Madu Deli Hijau’ indicates a very tight relationship, with a value of 0.000. The psbA-trnH intergenic spacer proved to be insufficient in differentiating the S. samarangense cultivars from Demak regency, mostly because to its low capacity to discern between the wax apple cultivars. Keywords: Demak, psbA-trnH intergenic spacer, Syzygium samarangense, wax apple